To solve the equation \(-2 - 8x = 4x - 2\), follow these steps:
-
Combine like terms: First, let's rearrange the equation to isolate the variable terms on one side. Add \(8x\) to both sides:
\[ -2 = 4x + 8x - 2 \]
This simplifies to:
\[ -2 = 12x - 2 \]
-
Add 2 to both sides: Now, we can eliminate the constant term on the right side. Add \(2\) to both sides of the equation:
\[ -2 + 2 = 12x - 2 + 2 \]
This simplifies to:
\[ 0 = 12x \]
-
Solve for \(x\): To find \(x\), divide both sides by \(12\):
\[ x = 0 \]
Thus, the solution to the equation \(-2 - 8x = 4x - 2\) is:
\[ \boxed{0} \]